Survey of project management methods which employed by fixed position layout in Malaysia - Siti Raihana, Shahadan (2012)
This thesis presents the survey on the project management methods which employed in fixed-position layout in Malaysia. The objectives of this research are to investigate the type of project management methodology and tools, the factors considered in project management methods and the performance of project management methods implemented in fixed- position layout (construction) in Malaysia. A questionnaire survey about project management methods were conducted at construction companies. Critical path method (CPM), Program Evaluation & Review Technique (PERT) and graphical evaluation & review technique (GERT) have been chosen as predictors in order to predict which project management method most suitable to be employed in fixed-position layout. The survey shows that the most significant method is CCPM and for tools is PERT followed by CPM and lastly GERT. CPM and PERT analysis were implemented to one of the construction project. As a conclusion, by having a good project management system such as CPM and PERT, the fixed position layout industry can strive for better improvement, redefine its image and steer itself in meeting a success in near future.